Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/fractalfract5040146
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Three Factors on Mass Loss and Surface Fractal Dimension of Concrete in Sulfuric Acid Environments

Abstract: When exposed to sulfuric acid environments, the service life of concrete structures would be reduced due to the high alkalinity of concrete. The influence of three factors including water/cement ratio, the pH value of the solution, and the chemical composition of the aggregate on the resistance of concrete subjected to sulfuric acid has been widely investigated by previous researchers. This paper aims to investigate the influence of these three factors on the durability evaluation indicators including mass los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…Yin et al [5] conducted experiments to compare the impact of different sulfuric acid concentrations on concrete corrosion and revealed that higher sulfuric acid concentrations resulted in more pronounced concrete damage. Xiao et al [6] assessed the mass loss and surface roughness of specimens subjected to sulfuric acid corrosion under different conditions and indicated that the sulfuric acid concentration has a more substantial influence on the corrosion process than the water/cement ratio and aggregate composition. Shariati et al [7] revealed that an increase in the content of coal waste (CW), which is used as a substitute for aggregates in concrete, leads to reduced resistance to sulfuric acid corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, acid degradation alone poses a significant obstacle in the long term to the durability of concrete in structures such as biogas and water treatment [37,38]. The sulfate attack is a widespread cause of harm to the durability of concrete.…”
Section: Introductionmentioning
confidence: 99%